Reformatoriese perspektiewe op die volksverteenwoordigende Standewese en politieke verset: Middeleeuse aanknopingspunte, post-Calvinistiese begronding en ontwikkelinge in Marnix van St. Aldegonde se politieke geskrifte - Raath, Andries (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2023)
By the time of the Reformation, it had already been well established that peace and justice in the political life is best accomplished when the membra et corpore of the state function in harmony (John of Salisbury (1120-1180)); in accordance with the measure set by the law, the princeship must establish the different parts of the State, equip them with their officia, reward and punish them, conserve them, promote their co-operation and prevent disturbance among them (Marsilius of Padua (died after 1342)), and the power of making laws are exercised by bodies representing the whole people under which stand the three estates (Clergy, Nobles and People) which regulate the special affairs of the provinces (Nicholaus of Cusa (1401-1464)). These principles found support from Calvin. His distinction between kings and tyrants focused on two aspects: tyrants rule against the will of their subjects and exercise power without restraint. To Calvin the just ruler acts as praeses legum et custos: upholding and guarding the laws. The just ruler acts as upholder and enforcer, that is to say, of laws that already exist, rather than the deviser of new ones. The first duty of the subjects towards magistrates is to think most honourably of their office, which indeed they should recognize as a jurisdiction bestowed by God, and on that account to esteem and reverence them as ministers and representatives of God. In insisting on the duty of obedience, Calvin had of course no more intention than Luther had of denying that there are occasions when we must obey God rather than men. But on his view, as on Luther’s, these cannot entitle private men to take up arms against their rulers. At best, there may be magistrates who happen to be appointed to restrain wicked rulers; ephors, tribunes and such power as the three estates exercise in every realm when they hold their chief assemblies. This exception, pregnant with momentous possibilities for later Calvinism, was all that Calvin would allow. The Magdeburg Confession (1550) casts the doctrine of the leser magistrates in a form superceding Calvin’s views on passive disobedience: All magistrates, higher and lower, possess delegated authority from God; lesser magistrates also have a duty to oppose the superior magistrate-turned-tyrant when he makes laws contrary to the law of God. This doctrine of the constitutional role of lesser magistrates served as a springboard for the Calvinist political and theological leader, Marnix of St. Aldegonde (1527-1589), during the early stages of the Dutch Revolt, to make freedom of conscience and civil liberties the most important concerns of the lesser magistrates in performing their constitutional duties of protecting the subjects against tyranny – an important step in the development of Reformational constitutional resistance theory.